ALLEVIATING THE SALT STRESS EFFECTS IN Salvia splendens BY HUMIC ACID APPLICATION - Zahra Karimian; Leila Samiei; Jafar Nabati (Acta Scientiarum Polonorum: Hortorum Cultus, 2019)
Salt stress is a serious problem in urban landscape of arid and semi arid regions. To overcome the adverse impacts of salinity, the application of organic matter and plant nutrients in the growth media for improving of plant growth is essential. An experiment was conducted in order to determine the response of Salvia splendens to salinity levels and also the role of humic acid in the salt stress alleviation. In the current experiment five salinity (0, 20, 40, 60, and 80 mM NaCl) and three humic acid (0, 100, 500 and 1000 mg l−1) treatments were prepared. The effects of these treatments were investigated on some growth parameters, physiological characteristics and also biochemical compounds. The results indicated that the growth parameters decreased in saline-treated plants than control plants. Different salinity levels significantly affected relative water content, evaporation rate and also electrolyte leakage. Salinity caused the increase in proline, malondialdehyde, sugar content, DPPH, total phenol content and decrease in chlorophyll, compare to the control plants. Application of humic acid on Salvia splendens, decrease leaf area and plant height compared to the control plants. Thus, regarding the growth parameters, it is probable that the effect of humic acid on the biochemical compounds is similar to salinity effect. The findings suggest that Sage is a sensitive ornamental plant to salinity and humic acid (in the studied levels) could not alleviate the negative effects of salt stress on this plant.